Deflowering as a Tool to Accelerate Growth of Young Trees in Both Intensive and Super-High-Density Olive Orchards - Franco Famiani; Nicola Cinosi; Andrea Paoletti; Daniela Farinelli; Adolfo Rosati; Enrico Maria Lodolini (Agronomy, 2022)
In 2019–2020, trials were carried out in both intensive (cultivar Moraiolo) and super-high-density (cultivar Sikitita) young olive orchards to drastically reduce early production and, consequently, accelerate tree growth. Different concentrations of naphthaleneacetic acid (NAA) (0 ppm–control, 20 ppm, 40 ppm, 80 ppm, 160 ppm and 250 ppm) were applied at full bloom (open flowers > 80%), using a shoulder sprayer, and their effects on vegetative growth and reproductive behavior were evaluated, also compared to manually deflowered trees. The treatments with NAA reduced fruit set (down to values close to zero) compared to the control, and the reduction was correlated with the NAA concentration. In particular, 160 ppm virtually eliminated fruit set and thus production in both Moraiolo and Sikitita cultivars. In Moraiolo, 160 ppm NAA and manual deflowering determined similar shoot and trunk growths, which were greater than in control trees. Application of 160 ppm NAA for two consecutive years gave a progressively higher increase in trunk growth compared to the control. In conclusion, in young olive trees, the treatment with 160 ppm NAA at full bloom practically eliminated fruit set and production, with a parallel great increase in vegetative growth. This can be exploited as a powerful technique to accelerate the growth of young olive trees in both intensive and super-high-density orchards, as well as in nurseries. A more rapid transition to the adult stage/size of the trees and to full production of the orchard allows us to anticipate the use of mechanical harvesting and the recovery of the planting investment.